Plant-Based Meats, Human Health, and Climate Change - van Vliet, Stephan; Kronberg, Scott L.; Provenza, Frederick D. (Frontiers in Sustainable Food Systems, 2020)
There is wide scale concern about the effects of red meat on human health and climate change. Plant-based meat alternatives, designed to mimic the sensory experience and nutritional value of red meat, have recently been introduced into consumer markets. Plant-based meats are marketed under the premise of environmental and human health benefits and are aimed to appeal a broad consumer base. Meat production is critiqued for its overuse of water supplies, landscape degradation, and greenhouse gas emissions—depending on production practices, environmental footprints may be lower with plant-based meat alternatives. Life-cycle analyses suggests that the novel plant-based meat alternatives have an environmental footprint that may be lower than beef finished in feedlots, but higher than beef raised on well-managed pastures. In this review, we discuss the nutritional and ecological impacts of eating plant-based meat alternatives versus animal meats. Most humans fall on a spectrum of omnivory: they satisfy some nutrient requirements better from plant foods, while needs for other nutrients are met more readily from animal foods. Animal foods also facilitate the uptake of several plant nutrients (zinc and iron), while plant nutrients can offer protection against potentially harmful compounds in cooked meat. Plant and animal foods operate in symbiotic ways to improve human health. The mimicking of animal foods using isolated plant proteins, fats, vitamins, and minerals likely underestimates the true nutritional complexity of whole foods in their natural state, which contain hundreds of nutrients that impact human health. Novel plant-based meat alternatives should arguably be treated as meat alternatives in terms of sensory experience, but perhaps not as true meat replacements in terms of nutrition. If consumers wish to replace some of their meat with plant-based alternatives in the diet (a “flexitarian approach”) this is unlikely to negatively impact their overall nutrient status, but this also depends on what other foods are in their diet and the life stage of the individual.